Plant-Soil Feedbacks for the Restoration of Degraded Mine Lands: A Review - Zhu, Shi-Chen; Zheng, Hong-Xiang; Liu, Wen-Shen; Liu, Chang; Guo, Mei-Na; Huot, Hermine; Morel, Jean Louis; Qiu, Rong-Liang; Chao, Yuanqing; Tang, Ye-Tao (Frontiers in Microbiology, 2022)
Much effort has been made to remediate the degraded mine lands that bring severe impacts to the natural environments. However, it remains unclear what drives the recovery of biodiversity and ecosystem functions, making the restoration of these fragile ecosystems a big challenge. The interactions among plant species, soil communities, and abiotic conditions, i.e., plant-soil feedbacks (PSFs), significantly influence vegetation development, plant community structure, and ultimately regulate the recovery of ecosystem multi-functionality. Here, we present a conceptual framework concerning PSFs patterns and potential mechanisms in degraded mine lands. Different from healthy ecosystems, mine lands are generally featured with harsh physical and chemical properties, which may have different PSFs and should be considered during the restoration. Usually, pioneer plants colonized on the mine lands can adapt to the stressful environment by forming tolerant functional traits and gathering specific soil microbial communities. Understanding the mechanisms of PSFs would enhance our ability to predict and alter both the composition of above- and below-ground communities, and improve the recovery of ecosystem functions in degraded mine lands. Finally, we put forward some challenges of the current PSFs study and discuss avenues for further research in the ecological restoration of degraded mine lands.